The Genetics of Papillary Microcarcinomas of the Thyroid: Diagnostic and Prognostic Implications - Cunha Rodrigues, Ana; Penna, Gustavo; Rodrigues, Elisabete; Castro, Patrícia; Sobrinho-Simoes, Manuel; Soares, Paula (Current Genomics, 2017)
Papillary microcarcinoma of the thyroid (mPTC) is defined by the WHO as a papillary thyroid cancer measuring 10mm or less in diameter and it is nowadays a topic of intense debate among the members of the medical community due to its apparent “epidemic” rise. Although these tumors follow almost always an indolent clinical course and carry an excellent prognosis, it is known that a small subset may display a potentially aggressive behavior. Nevertheless, we still lack an accurate way of predicting those which will cause significant disease. In an attempt to address this problem, a number of clinico-pathologic features have been studied as poor prognostic markers in mPTC, and their association with known genetic alterations in thyroid cancer has been evaluated. Herein we review the present knowledge concerning mPTC's genetic profile, namely the prevalence of BRAF (V600E), RAS and TERT promoter mutations and RET/PTC and PAX8-PPARG rearrangements and report the results of the evaluation in the putative prognostic value of these genetic alterations in mPTC.
Keywords: mPTC